Comparison of back-scattering properties of electron emission materials - Insepov, Z.; Ivanov, V.; Jokela, S.; Wetstein, M. (Proceedings of 2011 Particle Accelerator Conference, New York, 2011)
We use “microscopic” Monte Carlo (MC) simulations, empirical theories, and comparison with experiments to identify the influence of back-scattered electrons and the saturation effect on the emissive properties of materials and to study the gain and transit times for various microchannel plates (MCPs). We have applied this method to Al2O3 and MgO emissive materials of various thickness and surface quality. The experimental secondary emission yield (SEY) data were obtained at normal electron impacts and were used as the reference data for adjusting our MC simulations. The SEY data were calculated at oblique angles of the primary electrons in the interval of 0-80°. The energy dependence of backscattered electron coefficients (BSCs) for various primary electron incidence angles was calculated by MC for both materials, and the results were compared with experimental “average” values obtained in the literature. Both SEY and BSC data were used as input files to our “macroscopic” trajectory simulation, which models MCP amplifiers as whole devices and is capable of gain and transit time calculations. The deposition and characterization experiments were conducted for the Large Area Picosecond Photodetector project at Argonne National Laboratory.
Keywords: Monte Carlo (MC) simulation; back-scattered electrons